A Struggle to Change the World System : a realist and neorealist analysis of the Brazilian, Chinese and Russian strategies. - Iličová, Ivana (2016)
The system changed after the Cold War and the bipolar structure ended and left the USA as the only superpower. The question of the 21st century what is the current structure and how the emerging powers are becoming more important and how it can change the structure and rise their dominance in the multipolar world. The analyzed actors Brazil, China and Russia through their strategies are offering the possible system changes and configurations for the near future from the realist/neorealist perspective.